THE COURSE OF TRICHURIASIS AS PARASITOSIS OF SHEEP DIGESTIVE SYSTEM - Soroka, N. M. (Scientific Progress & Innovations, 2020)
Sheep farming in most countries of the world, including Ukraine, occupies a special place among live- stock farming industries and is a supplier of such products as mutton and wool. Sheep are characterized by good breeding qualities, high reproductive capacity and adaptive properties. Parasitic diseases are one of the factors hindering the development of sheep farming. Among their diversity, one of the leading places is occupied by nematodoses of the animals’ digestive system, including trichuriasis, which can occur in the form of associative invasions. The studies were conducted at the Laboratory of the Department of Parasitol- ogy and Tropical Veterinary Medicine of the National University of Life and Environmental Sciences of Ukraine and on private farms of Kyiv region. A total of 258 coproovoscopic studies of sheep were conducted. According to the results of parasitological studies, it was found that sheep trichuriasis is a common invasion on the territory of individual farms in Kyiv region, with an average invasion intensity of 35.7 %. Trichurises were found to be parasitizing mainly in the digestive canal in the form of associative invasions (69.6 %). Nematodes (strongyloideses, strongylates of the digestive system) and cestodes (moniezes) were the main co- members of trichurises. Two-component mixed invasions (65.6 %) were most often diagnosed in case of sheep trichurosis, and three-component associative invasions were detected less frequently (34.4 %). 5 va- rieties of mixed invasions were revealed in sheep infected with trichuriasis causal agent. As to two- component associative invasions, simultaneous parasitizing of trichurises and strongylates in the digestive system (31.3 %), trichurises and moniezes (23.4 %), as well as trichurises and strongyloideses (10.9 %) was detected. Of the three-component mixed invasions, the simultaneous parasitizing of trichurises, moniezes, and strongylates of the digestive system was most commonly diagnosed (21.9 %). Trichuriasis- strongylodosis-strongylatosis mixed invasion made a smaller proportion (12.5 %). The obtained data on the associative course of sheep trichuriasis together with nematodoses and cestodoses of the digestive system will enable to choose the correct anti-helminthic preparations, which will increase the effectiveness of pre- ventive measures.